2018
DOI: 10.1080/17429145.2018.1483033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ascorbic acid and 24-epibrassinolide on physiological characteristics of pot marigold under water-stress condition

Abstract: Water deficit is considered as a major limiting environmental factor for plant growth and yield. To ameliorate the adverse effects of water restriction, an experiment was conducted in the research field of Mohaghegh Ardabili University in two successive years (2014 and 2015). Foliar spraying of different concentration of epibrassinolide (EBL) (0, 10 −8 , and 10 −7 M) and ascorbic acid (AsA) (0 and 10 mM) was carried out and water-stress trials included 50 and 100 mm evaporation from class A pan. Water stress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
(41 reference statements)
4
11
0
Order By: Relevance
“…RWC is a key indicator to describe the water relation and physiological function in plants. Previous studies showed RWC as an eminent trait to measure stress tolerance (Hemmati et al 2018;Dapanage and Bhat 2018). We observed the high RWC in Zafar and Hyola4815.…”
Section: Discussionsupporting
confidence: 58%
“…RWC is a key indicator to describe the water relation and physiological function in plants. Previous studies showed RWC as an eminent trait to measure stress tolerance (Hemmati et al 2018;Dapanage and Bhat 2018). We observed the high RWC in Zafar and Hyola4815.…”
Section: Discussionsupporting
confidence: 58%
“…Similar results have been reported by Medeiros et al [57], who found that there was an increase in APX activity in sugarcane using 20 mM proline. Furthermore, ASA foliar application increased CAT, SOD and Calendula POX activity [58]. Increased CAT, SOD and POX activity could effectively detoxify harmful ROS effects [59].…”
Section: Changes In Enzymatic Antioxidantsmentioning
confidence: 94%
“…BRs significantly increased the water uptake and membrane stability with higher carbon dioxide and nitrogen assimilation in wheat plants under stress that can be seen in response to drought tolerance only (Krishna, 2003; Wang et al ., 2015). Another piece of evidence indicated that EBL application can improve plant photosynthetic pigments, osmolytes production, antioxidant enzyme activities, and seed yield under drought stress (Hemmati et al ., 2018; Zafari et al ., 2020). However, the research regarding the effects of EBL under drought stress in plants, especially, in wheat needs more attention.…”
Section: Introductionmentioning
confidence: 99%